PENETAPAN KADAR KALSIUM PADA SUSU BUBUK BERMEREK “H” SECARA TITRASI KOMPLEKSOMETRI - MUSTAFA R LUBIS (LP2MTBM MAKARIOZ, 2018)
Powdered milk is a dairy product obtained by reducing a large portion of water through the process of drying fresh pasteurized milk or recombined milk, with or without the addition of vitamins, minerals, and food additives that are permitted. Powdered milk includes fatty, low fat and nonfat milk powder (BSN, 2006). The mix of branded